PERATURAN KOMISI YUDISIAL: JENIS, HIERARKI, DAN IMPLIKASI JUDICIAL REVIEW - Hazmi, Raju Moh; Haskar, Edi (Ensiklopedia of Journal, 2025)
Abstract: This research aims to provide an explanation of the conception of the Judicial Commission Regulation; whether it falls into the category of legislation or not. Linearly, as a logical consequence of the hierarchical nature of the legislative system, where is the location/position of the Judicial Commission Regulation when analysing its content. This issue arises because the Judicial Commission Regulation does not explicitly appear in the hierarchy of laws and regulations. Therefore, it has implications for what judicial institution has the authority to test the material validity of the Judicial Commission Regulation if it conflicts with the laws and regulations above it. To unravel these legal issues, normative research is used through conceptual approaches and legislation. The data used is secondary data which includes primary, secondary, and tertiary legal materials. Analysis of the data will be presented descriptively qualitatively through the content analysis method. The results of this research found that (1) theoretically, the Judicial Commission Regulation is not included in the category of laws and regulations but falls into the category of internal regulations, but because it is ordered to be formed by law, it is considered to be included in the category of laws and regulations (2) the Judicial Commission Regulation can be equated with the Presidential Regulation in terms of content, so it is equal to the Presidential Regulation in the hierarchical construction of laws and regulations, (3) the Supreme Court is the institution that has the authority to materially examine the Judicial Commission Regulation. This research recommends that improvements should be made by issuing Judicial Commission Regulations that are no longer considered laws and regulations, but rather internal regulations. Keywords: Judicial Commission Regulation; Hierarchy of Laws and Regulations; Judicial Review.